Steinernema feltiae Filipjev (Rhabditida: Steinernematidae) and selected insecticides: Integrated effects on survival, feeding activity, and development of Ostrinia furnacalis Guenée (Lepidoptera: Crambidae) - Chen Ge; Sohail Abbas; Wei Hongye; Geng Mengchen; Xue Xiyao; Li Yuexuan; Li Bo; Bilal Ahmed; Aleena Alam; Khalid Ali Khan; Hamed A. Ghramh; Li Qiyun; et al. (Crop Protection, 2026)

Beyond fibrous alignment: Cross-scale assembly and mesoscopic continuity of edible mushroom proteins and mycelial materials in meat analogues - Ge Wang; Zhi Cheng; Yuxin Chen; Bo Yu; Qiping Zhan; Xiao Chen; Liyan Zhao (Trends in Food Science & Technology, 2026)

Transcription factor TaPIL1-mediated iron accumulation in wheat - Yanjun Meng; Zijia Tian; Jiayi Fan; Zhouxiang He; Bo Yu; Changqing Du; Tiancai Guo; Qiang Ge; Guozhang Kang (Plant Science, 2026)

Chain mail-inspired adaptive protection architecture using mechanically interlocking lattice - Jiahui Ge; Zhenlong Chao; Longtao Jiang; Ming Zhu; Bo Geng; Tian Luo (Engineering Structures, 2026)

Rapid phase separation assisted hydrogel evaporator for solar desalination and water environmental purification - Jianbo Zhang; Jinming Yu; Tongyu Zhang; Zhenjie Ma; Yutian Wang; Bo Ge; Hui Zhao; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Desalination, 2026)

Lattice carbon-induced electronic regulation of AlCo2O4 spinels for boosting toluene oxidation - Dadao Wang; Xueqin Yang; Mimi Wu; Menglan Xiao; Yanhu Zhang; Mianmian Zhang; Xiuhong Zhu; Guangxin Ru; Yucong Guo; Bo Shi; Xiaolin Yu; Maofa Ge (Journal of Environmental Chemical Engineering, 2026)

Proteomics-guided multivalent capture and integrated amplification enable profiling of tumor-derived extracellular vesicles in gastric cancer - Ke Ge; Yongan Ren; Pengcheng Wang; Guangzhong Ma; Bo Yao; Changku Jia; Yuanyu Wang; Kai Ye (Chemical Engineering Journal, 2026)

Eco-hydrological processes in controlling vertical and lateral carbon fluxes in a subtropical salt marsh: Insights from modeling and scale-resolved analysis - Ke-Hua Zhu; Li-Shan Tan; Guan-Xun Wang; Li-Ming Xue; Zeng-Feng Li; Hua-Yu Chen; Qing Lyu; Bo-Fei Li; Wei Zhao; Christian Schwarz; Zhen-Ming Ge (CATENA, 2026)

Integrated sludge resources hierarchical recovery: enhancing VFAs production through pilot scale liquid-state anaerobic fermentation by sludge residues-based biochar - Jing Zhang; Dong-Shan Yang; Jia-Yu Yang; Yun-Yi Song; Nan Wu; Tian Pu; Ge Zhu; Hong-Bo Liu; He Liu (Bioresource Technology, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Filler-free, small-molecule-induced hydrogen-bond reconstruction enables enhanced piezoelectric performance in polyamide 11 - Shu-Dan Ge; Xin Li; Min Jiang; Shi-Huan Tan; Xian-Yue Xiang; Si-Si Wang; Hai-Bo Zhao; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Fine-scale mapping of built-environment carbon emissions: A multi-source data fusion and explainable machine learning framework for high-density urban regions - Ge Shi; Haoran Tang; Wei Wang; Chuang Chen; Jiantao Shi; Bo Wang; Lin Sun (Building and Environment, 2026)

3D-DEM assessment of seismic instability in a naturally fractured wedge rock mass based on terrestrial laser scanning and DFN modeling - Yunfeng Ge; Bin Hu; Huiming Tang; Bo Lu; Qian Chen; Changdong Li (Bulletin of Engineering Geology and the Environment, 2026)

A Wind Data Quality Control Algorithm Utilizing Deep Learning-Based Association Test Rules - Ruidi Ma; Song Gao; Fan Jiang; Bo Yu; Haoqiang Tian; Yanchen Song; Yong Ge; Dianjun Ren; Chenxu Wang (Journal of Marine Science and Engineering, 2026)
Harnessing the powerful learning and modeling capabilities of artificial intelligence, this study introduces a deep learning-driven wind data quality control algorithm that employs correlation verification rules. By constructing a Dual-Track Information Fusion Network (DTF-Net), it captures local temporal variations in wind speed via the temporal track and uncovers physical coupling relationships among temperature, pressure, wind direction, and other variables through the global track. Integrating dynamic three-standard-deviation spike detection with 3δ-RMSE spatial validation based on deep learning predictions, the algorithm enables multi-dimensional collaborative anomaly detection in the absence of neighboring stations. Experimental findings demonstrate that the proposed method achieves Mean Absolute Errors (MAE) of 0.217, 0.398, and 0.462 for 1 h, 12 h, and 24 h wind speed forecasts, respectively, representing a 3.8–61.3% reduction compared to general-purpose models like AutoFormer, ITransformer, and FiLM. The anomaly detection rate for quality control ranges from 0.33% to 9.20%, effectively identifying data aberrations during buoy maintenance, equipment failures, and abrupt changes in short-term weather patterns. This study leverages the powerful learning and modeling capabilities of artificial intelligence to establish a novel and easily understandable intelligent quality-control paradigm for sparse ocean observation networks, providing direct practical value for improving the quality of marine meteorological data assimilation.

Predefined-time global prescribed performance tracking of ASV via adaptive event-triggered control - Peng Chen; Tao Han; Bo Xiao; Yuan Tan; Xi-Sheng Zhan; Ming-Feng Ge (Ocean Engineering, 2026)

Intelligent Vessels Localization Based on Adaptive Correlation Information Filter Network in Complex Marine and Port Environments - Lei Yan; Wei Zeng; Zhixin Xia; Bo Meng; Junli Ge; Deming Kong (Journal of Marine Science and Engineering, 2026)
Accurate and robust localization is essential for intelligent vessels operating in complex marine and port environments. However, single-sensor localization is often affected by limited observation range, environmental occlusion, local interference, and sensor degradation. Although multi-sensor fusion can improve localization reliability, unknown cross-correlated measurement noise arising from shared disturbances, time synchronization errors, communication delays, and inconsistent fusion rates may degrade traditional information-filter-based fusion methods. To address this problem, this paper proposes an Adaptive Correlation Information Filter Network (ACIFNet) for multi-sensor fusion localization of intelligent vessels. ACIFNet preserves the recursive structure of the extended information filter and uses a Transformer-based network to learn adaptive information-domain fusion weights, thereby compensating for unknown inter-sensor correlations without explicitly estimating the full correlation covariance matrix. Experiments on constant-velocity, coordinated-turn (CV), and three-degree-of-freedom vessel motion models, together with a real-world restricted-waterway dataset, demonstrate that ACIFNet achieves higher localization accuracy and stability than Edge Incorporative Fusion (EIF)-inexact fusion, measurement fusion, and KalmanNet. In the CV and three-degree-of-freedom experiments, ACIFNet reduces the mean RMSE by 48.7%, 23.2%, and 26.1%, respectively, compared with KalmanNet. On the real-world dataset, ACIFNet achieves a mean position error of 9.90 m, an RMSE of 11.24 m, and a cross-track error of 8.72 m. These results show that ACIFNet effectively combines the interpretability of information filtering with the adaptive representation capability of neural networks for robust multi-sensor fusion localization under unknown cross-correlated measurement noises.

From green tide disaster to green resource: a multidisciplinary review of research progress and future prospects on Ulva prolifera - Zhongwei Chen; Zhongzhen Chen; Chengjuan Cao; Binbin Wang; Haibo Feng; Yuehao Ge; Bo Yang (Frontiers in Marine Science, 2026)
Ulva prolifera is the primary causative species of large-scale green tides in the Yellow Sea, posing recurrent threats to marine ecosystems and coastal economies. In recent years, research has undergone a fundamental shift from disaster control toward resource utilization. This multidisciplinary review synthesizes progress across the entire chain of green tide management, focusing on advances in monitoring and prediction. These include multi-source satellite remote sensing with deep learning, coupled hydrodynamic-ecological models for bloom forecasting, and eDNA-based early detection of micropropagules, alongside insights into ecological and physiological mechanisms such as allelopathic competition, nutrient-driven rapid growth, and stress adaptation traits that underpin bloom dominance. Besides, we also highlight breakthroughs in germplasm and cultivation, notably natural protoplast-based clonal propagation and the potential for genetic improvement using synthetic biology, alongside high-value resource utilization through the extraction of bioactive polysaccharides, the discovery of a thermostable ulvan lyase for efficient enzymatic processing, and the exploration of biomass for functional foods, pharmaceuticals, bioenergy, and biomaterials. This review further examines microbial degradation, including active microbial community succession and key degraders that transform organic matter and influence carbon cycling, and concludes with industrialization prospects centered on a closed-loop “early warning–precise interception –high-value conversion” framework. Unlike previous reviews that focused on individual aspects, this work explicitly linked ecological drivers to biotechnological applications and industrial feasibility. We critically examined how these domains connected, identified knowledge gaps, and proposed a roadmap for establishing U. prolifera as a model species for the marine bioeconomy. This integrated perspective transforms an environmental threat into a sustainable green resource.

Advances in Mechanism Decoupling of Cavitating Jet Impingement and Multi-Source Measurement Techniques: A Review - Ge Zhu; Bo Liu; Xiaoyu Bu; Wenjun Zhou; Yongkang Xu; Xuanjun Wang (Journal of Marine Science and Engineering, 2026)
Cavitating jet impingement is a key phenomenon in marine and ocean engineering that is responsible for cavitation-induced material erosion while also being harnessed for surface treatment applications. However, decoupling these concurrent effects is challenging since hydrodynamic jet pressure, microjet impacts, and shockwave emissions often coincide in space and time, making it difficult to isolate their individual contributions. To address this challenge, this review surveys recent advances in measurement techniques designed to decouple these overlapping effects. It highlights multi-source synchronous measurement methods, such as high-speed optical imaging and broadband piezoelectric pressure sensing combined with advanced signal and image processing, to capture mechanism-specific signatures. The review treats mechanism decoupling as a linked task of mechanism identification, mechanism attribution, and contribution quantification and synthesizes the literature under distinct criteria, such as energy, peak pressure, and damage dominance. It shows that synchronized multi-source diagnostics improve attribution reliability but that true quantitative decoupling remains limited by configuration dependence, inconsistent normalization, and a lack of benchmark evaluation criteria.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Depolymerization mechanism of polybutylene succinate in subcritical water: Visual phase change and product distribution - Bo Xiao; Mian Hu; Jia-Yi Dong; Ya-Ge Zhang; Zhi-Gang Shen; Yi Liu; Jie-Xin Wang; Ziyan Pan; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

Reducing wheat grain Cd via harnessing indigenous microbiota in weakly alkaline soil - Chenghao Ge; Yixuan Wang; Wenyan Ma; Hong-Bo Li; Jingxia Guo; Hafiz Adeel Ahmad; Yan Gao; Dongmei Zhou (Plant and Soil, 2026)

Flexible SERS tape: A plasmonic hybrid of AuNPs and layered K2Ti8O17 nanowire network for on-site detection of pesticide residues - Lin Xu; Mingru Cui; Zhongqi Ge; Ruikang Zou; Cong Wang; Pengfei Ni; Xi Huang; Bo Zhong; Lijuan Wang (Analytica Chimica Acta, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

PG-DyMamba: a physics-guided dynamic graph Mamba network for significant wave height prediction - Fan Jiang; Yinzhu Zang; Ruidi Ma; Bo Yu; Hui Li; Song Gao; Yong Ge; Dianjun Ren (Frontiers in Marine Science, 2026)
Accurate prediction of Significant Wave Height (SWH) is vital for marine engineering safety, yet balancing computational efficiency with physical consistency in long-sequence modeling remains a challenge for data-driven approaches. To address this, we propose the Physics-Guided Dynamic Graph Mamba Network (PG-DyMamba). By integrating oceanographic priors such as windwave relations, our Physics-Aware Graph Learner adaptively captures time-varying multivariate dependencies. Concurrently, the Mamba architecture processes long historical sequences with linear complexity. To ensure physical plausibility, the model employs a composite loss function based on energy conservation and fluid smoothness, effectively constraining predictions to adhere to fundamental physical laws. Empirical evaluations on Australia, NDBC, and North Sea datasets confirm that PG-DyMamba outperforms state-of-the-art baselines. Notably, the model achieves a 19.2% MSE reduction in 48-step prediction horizon on the Australia dataset, demonstrating its robustness for operational marine applications.

Data Fusion Framework for a High-Resolution Regional Dataset in the Western North Pacific - Lifu Fu; Chunling Zhang; Yijun Ge; Bo Shu; Ruoxiao Zhou (Journal of Marine Science and Engineering, 2026)
Based on the large volume of observational data obtained from Argo and several satellites, an increasing number of datasets are being developed and applied to oceanographic research. However, there are still problems such as sparse subsurface observations, insufficient parameters, and weak pertinence. This study provides a basic framework for high-resolution data fusion that focuses on the multi-source observations in the Western North Pacific. Multi-source observations from satellites, Argo floats, and historical in situ profiles are fused using a statistical model and a gradient-dependent optimal interpolation method. A daily gridded dataset with a 0.25° horizontal resolution is developed, which includes temperature, salinity, and currents. The results show that the correlation coefficients between the observations and the inverted profiles of temperature and salinity are about 0.99 and 0.94, respectively, with mean root mean square errors of about 1.27 °C and 0.13, respectively. In the Northwest Pacific Ocean, the most suitable parameter settings are a search radius of 1.5° in longitude and latitude, correlation scale constant of 0.25°, and relative observation error of 2. Consequently, the average RMSEs of the fused temperature and salinity fields are 0.43°C and 0.056, respectively. Compared with other reanalysis datasets, the product constructed in this study retains more high-frequency ocean signals, and its temperature error relative to XBT observations is also the smallest. Furthermore, the dataset effectively depicts the characteristics of marine dynamic processes such as the Kuroshio paths and mesoscale eddies.

Comparative evaluation of urine, whole blood, and serum as biological matrices for human biomonitoring of neonicotinoid insecticides and metabolites - Yuli Lin; Junye Bian; Kai Lin; Yiming Ge; Chiqun Shan; Bo Fu; Weizhong Chen; Tao Chen; Qinru Xiao; Bingjun Lu; Qunlin Xiao; Shaoyou Lu (Journal of Hazardous Materials, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Multi attribute refined identification of flood-affected bodies based on multi-source data fusion - Yutie Jiao; Zongkun Li; Wei Ge; Meimei Wu; Bo Wang; Yadong Zhang; Pieter van Gelder (Journal of Hydrology, 2026)

Development of high-efficient CuFeZnAl-based hydrotalcite catalyst for glycerol hydrogenolysis to 1,2-propanediol - Yuanyuan Ge; Yifan Ma; Zhikuan Lin; Zhihang Lai; Haijun Guo; Bo Chen; Hairong Zhang; Lian Xiong; Xinde Chen; Zhili Li (Journal of Environmental Chemical Engineering, 2026)

Increased heterogeneity of sedimentary potential silicate-solubilizing bacterial communities caused by cascade damming reduces community complexity but promotes stability - Juan Chen; Qihao Nie; Chao Wang; Peifang Wang; Yuansheng Zhu; Ge Cui; Han Gao; Bo Zhang; Shunqing Zhang (Journal of Environmental Sciences, 2026)

Elastic ceramic aerogels via multiscale structural engineering for thermal superinsulation in extreme environments - Zhen Xu; Junhua Zhang; Ling Xu; Feiyang Ni; Sihan Hu; Shengkui Tang; Lei Zhang; Nannan Ge; Bo Wu; Zhenzhen Xu; Dingsheng Wu; Quan Feng (Chemical Engineering Journal, 2026)

MMD-Net: A Vision-Language Perception Model for Maritime Object Detection and Application - Bo Shi; Zitao Wang; Tianyu Cao; Hong Zhao; Qiqi Ge (Journal of Ocean University of China, 2026)

Stability of Beach Nourishment Under Extreme Wave Conditions: Insights from Physical-Model Experiments and XBeach Simulations - Tingting Zhu; Bo Hu; Hao Wang; Hanbao Chen; Baolei Geng; Longzai Ge; Ruijia Jin (Journal of Marine Science and Engineering, 2026)
Beach nourishment is a widely adopted nature-based solution for coastal erosion; however, its design efficacy and morphodynamic resilience under extreme wave conditions remain inadequately quantified, posing challenges for coastal hazard assessment. This study integrates physical-model experiments and XBeach numerical simulations to investigate the hydrodynamic and morphodynamic behavior of nourished beaches subjected to typhoon-driven extreme wave conditions at a headland-bay beach on Meizhou Island, China. Physical-model experiments were conducted to examine shoreline response and sediment redistribution under extreme waves for three nourishment tests. XBeach simulations resolved wave-induced currents, water-level variations, and sediment transport processes, enabling continuous tracking of nearshore hydrodynamics and beach profile evolution for three nourishment tests during Typhoon Doksuri. Results indicate that nourishment geometry and groin configuration play a dominant role in wave breaking patterns, sediment transport pathways and erosion–deposition distributions. Groin positions strongly influence alongshore sediment transport. Relocating the groin to an accretional zone reduces lee-side erosion and promotes a more stable shoreline. Steeper nourishment foreshore slopes promote offshore wave shoaling and breaking, enhancing fast wave-energy dissipation, shifting erosion seaward and limiting landward erosion extent. Consistent responses from both experimental and numerical results demonstrate that nourishment stability under extreme wave conditions is better characterized by the combined effects of erosion extent, erosion length, erosion depth, erosion volume, and alongshore and cross-shore sediment redistribution. The integrated physical–numerical approach provides a practical framework for assessing beach nourishment stability during coastal hazard events and offers guidance for the design and evaluation of resilient beach nourishment in wave-dominated, typhoon-prone coastal regions.

Dual-facet modulation involving surface carboxyl functionalization and interlayer regulation by CQDs in g-C3N4 for enhanced xylose photooxidation - Shilian Yang; Juan Liu; Chao Huang; Ge Yuan; Bo Lu; Tingzhen Li; Emmanuel Iwuoha; Reverant Crispin; Kasim Ocakoglu; Ren Zou; Linxin Zhong; Xinwen Peng (Chemical Engineering Journal, 2026)

Similarity evaluation of seismic datasets by an adversarial validation framework based on deep learning - Shu-na Chen; Zhe-ge Liu; Shu-ying Ma; Jing-Bo Zhai; Ya-juan Xue (Applied Geophysics, 2026)

Inhibitors Enable Rapid Start-up and Stable Operation of Partial Nitrification: Effects, Mechanisms and Challenges - Yun Song; Xiaoyu Han; Shujun Zhang; Liang Zhang; Bo Wang; Da Kang; Zheng Ge; Yongzhen Peng (Journal of Environmental Sciences, 2026)

Mechanism of physicochemical changes in potato starch gel induced by citric acid-autoclaving for texture improvement and resistant starch formation - Linlin Cui; Xinzhu Wang; Shuhan Ge; Xia Li; Yu Wang; Bo Nan; Zhicheng Zhang; Yuhua Wang (Food Chemistry, 2026)

Generation, transformation and inhibition mechanism of hazardous waste flue coated materials during copper smelting process - Kai Fan; Haipei Zhang; Zhongming Jiang; Songhe Ye; Zhenqin Ge; Bo Li; Yonggang Wei; Shiwei Zhou; Hua Wang (Waste Management, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

The long-term practice of poplar-soybean intercropping under wide-row spacing arrangement enhances soil stoichiometric ratios and enzyme activities - Cheng Xu; Zhuangzhuang Qian; Bo Wang; Tao Yang; Xiaomin Ge; Hui Liu; Luozhong Tang (Agroforestry Systems, 2026)

Dam construction and nutrient enrichment led to simplification of riverine micro-food webs by weakening top-down control effect - Ge Cui; Juan Chen; Chao Wang; Peifang Wang; Bo Zhang; Shunqing Zhang; Qihao Nie (Journal of Environmental Management, 2025)

GRACE-derived spatiotemporal changes of terrestrial water storage in the major plateaus of China - Dong Wang; Bo-Hui Tang; Yingyun Li; Wei Fu; Zhitao Fu; Zhen Zhang; Zhongxi Ge (Global and Planetary Change, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Roll-to-roll fabrication of paper-tape electrochemical sensing devices for point-of-care testing - Xinghua Du; Ruping Liu; Yicheng Chen; Hongbo Shan; Lu Han; Yongsheng Cai; Lihui Ke; Jiafeng Chen; Li Wang; Bo Wei; Changjiang Ge; Minghua Du; et al. (Chemical Engineering Journal, 2025)

Anti-cystitis glandularis action exerted by glycyrrhetinic acid: bioinformatics analysis and molecular validation - Haiwei Hu; Yongbo Tang; Baotong Zhou; Shuangyan Chen; Jimin Su; Wei Zhong; Yuanyang Wei; Yipeng Huang; Bo Ge (Molecular Diversity, 2025)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

A Rayleigh distribution-based fatigue damage prediction model for offshore structures under bimodal responses - Haiyang Ge; Xiaozhou Guo; Xin Li; Qiangqiang Wei; Bo Wu (Ocean Engineering, 2025)

Creep deformation characteristics and microscopic mechanism of undisturbed soils of the landslide sliding zone in the Jinpingzi area - Ruihong Wang; Rui Zhao; Ge Zhang; Bo Lu (Bulletin of Engineering Geology and the Environment, 2025)

Poplar–wheat intercropping and fertilizer application significantly improve soil bacterial community characteristic and nutrient contents - Cheng Xu; Xiaopeng Liu; Zhuangzhuang Qian; Tao Yang; Bo Wang; Xiaomin Ge; Luozhong Tang (Applied Soil Ecology, 2025)

Potential tuning of polycrystalline piezoelectric component for effective energy-band structure and markedly enhanced H2 yield of photocatalytic component - Xinxin Jin; Yingshuang Zhang; Xiao Li; Peng Liu; Qinghao Ge; Zhihao Zhao; Xingzhang Li; Lige Gong; Zhiping Zhang; Dan Li; Feng-Ming Zhang; Limin Dong; et al. (Chemical Engineering Journal, 2025)

MOF-encapsulated fullerene solid solutions: Harnessing maximal host-guest interactions for visible-light photocatalytic hydrogen generation - Zehu Wang; Haibing Meng; Xiaolong Liu; Ningning Wu; Libin Yang; Bo Wu; Gang Li; Qiwen Liu; Jie Li; Jiechao Ge; Chunru Wang (Chemical Engineering Journal, 2025)

Development and evaluation of photolysis and gas-phase reaction scheme in EPICC-model: Impacts on tropospheric ozone simulation - Wending Wang; Huansheng Chen; Zifa Wang; Jie Li; Xueshun Chen; Fenfen Yu; Xiaohan Fan; Shuman Zhao; Bo Hu; Wei Wang; Xiao Tang; Zhe Wang; et al. (Atmospheric Environment, 2025)

The impacts of multi-scale urban environments on commuters’ active travel - Xin Ge; Feng Zhen; Bo Wang; Runlin Yang; Shimeng Shen (Transportation Research Part D: Transport and Environment, 2025)

Efficient conversion of granite powder: synthesis of zeolite A for Cu(II) adsorption from acidic electropainting wastewater - Chuyi Ge; Min Huang; Jing Li; Muyang Huang; Bo Chen; Shefeng Li; Shenxu Bao (Journal of Water Process Engineering, 2025)

Metatranscriptomic insights into nitrogen loss mediated by multi-kingdom microbial interactions in periphytic biofilms under imidacloprid exposure - Zuqiang Cao; Juan Chen; Chao Wang; Peifang Wang; Han Gao; Bingbing Feng; Bo Zhang; Rong Wang; Ge Cui (Journal of Hazardous Materials, 2025)

Thiazole-fused thiazoliniums with ketone warheads as covalent inhibitors targeting Cys44 of SARS-CoV-2 3CLpro - Qizhen Cao; Zhaoqin Zhang; Guanghao Zhu; Sanfeng Dong; Xue Sun; Yuqing Song; Ya Zhang; Tingting Cai; Xinben Zhang; Yong Zhang; Zhijian Xu; Ruisheng Xiong; et al. (Chemico-Biological Interactions, 2025)

Investigation of Near-Surface S-Wave Velocity Structure beneath the Epicenter and adjacent Area of the Jishishan Earthquake by using the Receiver Function - Fan-chang Meng; Ruo-ge Xu; Hui Sun; Bo Li; Yun Long (Applied Geophysics, 2025)

Study on expansion methods of the DC flow for transferring the temperature-distributed refrigeration power - Qiang Cao; Pengcheng Wang; Zhiping Wang; Yuji Chen; Lichun Ge; Peng Li; Qinyu Zhao; Bo Wang; Zhihua Gan (International Journal of Refrigeration, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

hsa_circ_0099682 exacerbates the development of diabetic retinopathy by promoting pathological neoangiogenesis via the miR-125b-5p/HNRNPU axis - Ge Yang; Mei Xu; HongWei Zhang; Bo Zhang; YuLian Xie; YueHua Chen; Qin Hu; ZiYu Luo; Jie Lin; ZhengWen Qin (Journal of Molecular Histology, 2025)

In vivo and in vitro degradation and biological toxicity studies of polyesters with varying degradation rates - Ze-Yang Zhang; Wei-Zhen Zheng; Zhi-Chao Zhen; Xiao Li; Ping-Li Wang; Bo Lu; Xiu-bin Yang; Dan Huang; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2025)

Rapid cross-linking of MoS2 photothermal layers and their assembly of interface evaporators for desalination and environmental optimization - Zekun Zhang; Xiuling Li; Guangqi Liu; Shuo Qi; Jing Lv; Bo Ge; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Desalination, 2025)

Maternal transcription factor OTX2 directly induces SETD1A and promotes embryonic genome activation in human pre-implantation embryos - Tianlei Zhang; Ziyan Peng; Fei Meng; Zhuo Li; Junru Chen; Qinwei Zhou; Lizhi Leng; Hao Bo; Guangxiu Lu; Yun Deng; Feng Gu; Ge Lin (Science China Life Sciences, 2025)

Isolation of two peptaibols with potent antimicrobial and cytotoxic activities from the mangrove endophytic fungus Trichoderma lentiforme ML-P8-2 - Yihao Yin; Ge Zhu; Jianying Wu; Zhigang She; Jie Yuan; Bo Wang (Natural Product Research, 2025)

Heat-triggered CRISPR/Cas12a microspheres for one-pot assays - Siying Xie; Shan Shao; Jin Wang; Jing Qu; Ying Cai; Xingyan Lai; Nan Min; Lidan Zhang; Yan Shi; Tingdong Li; Xiaomin Zhang; Bo Peng; et al. (Science Bulletin, 2025)

Optimization of surface modification conditions of jute powder and study of its adsorption behavior and mechanism for Pd(II) - Man Lu; Manman Ge; Yong Li; Guozhen Wang; Xinke Kang; Haiyan Wu; Ling Tan; Haigang Dong; Jianping Xie; Bo He (Journal of Environmental Chemical Engineering, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

Mechanistic insights into electrode autotrophic denitrification: Isolation and electron transfer of Paracoccus versutus HD1 in denitrifying bioelectrochemical systems - Bo Cao; Ting Zhao; Yanhong Ge; Hongyu Zhao; Beizhen Xie; Hong Liu (Chemical Engineering Journal, 2025)

Synthetic phenolic antioxidant contamination in farmland soils induced by mulching films: Distribution and transformation pathways - Shanxing Wu; Meng Gao; Bo Fang; Lili Rong; Zhanpeng Ge; Hao Chen; Yiming Yao; Yu Wang; Hongwen Sun (Journal of Hazardous Materials, 2025)

Permafrost thawing characterization in engineering scale by multi-geophysical methods: A case study from the Tibet Plateau - Junkai Ge; Huaifeng Sun; Rui Liu; Zhiyou Huang; Bo Tian; Lanbo Liu; Ziqiang Zheng (Engineering Geology, 2025)

Efficient preparation of potassium humate from waste vegetable leaves: Development of a Cu2O@HAK catalyst and innovative application of hydrothermal method - Jiamin Qi; Jiliang Zheng; Yatang Dai; Bo Yang; Haohao Bian; Xinyu Chen; Shunyu Yin; Xiuling Yan; Xiaoyan He; Hongguang Zhao; Yanjie Ren; Changchun Ge; et al. (Journal of Environmental Chemical Engineering, 2025)

Ultra broadband emission toward white LED based on dysprosium double perovskites CsxRb3-xDyCl6-xIx - Xue Bai; Zongqing Jin; Guanjun Xiao; Bo Zou; Qingqin Ge; Nannan Shi; Liwei Jiang; Cheng Sun; Tao Xiong; Yinan Zhang (Chemical Engineering Journal, 2025)

Microglial membrane-coated nanoparticles for ACSL4-siRNA delivery in Parkinson’s disease - Heyue Lu; Bo Zhang; Min Ge; Juncheng Yu; Fei Ju; Jie Sun; You Lang Zhou; Lei Wang; Zhongzheng Jia (Chemical Engineering Journal, 2025)

Modeling diabetic cardiomyopathy using human cardiac organoids: Effects of high glucose and lipid conditions - Xiangyu Wang; Xin Tan; Ting Zhang; Shuai Xu; Yiyao Zeng; Anchen Xu; Xian Li; Ge Zhang; Yufeng Jiang; Hezi Jiang; Jili Fan; Xiaohong Bo; et al. (Chemico-Biological Interactions, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

Environmental DNA metabarcoding: Current applications and future prospects for freshwater fish monitoring - Shuaishuai Liu; Juan Chen; Ge Cui; Bo Zhang; Bingcheng Yan; Qihao Nie (Journal of Environmental Management, 2025)

Ultralow nano-hierarchical filler loadings enhance the energy storage performance of PEI-based nanocomposites - Zijun Mu; Jin Qian; Guanglong Ge; Simin Wang; Hairui Bai; Guohui Li; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Kinetics of methane hydrate formation in a 1200 ml unstirred reactor for natural gas storage - Kun Ge; Bo Gao; Wei Yu; Ye Tian; Xin Zhou; Jiaqi Wang (Fuel, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Parametric study on the methanol/diesel JCCI mode with dual-direct injection system in a light-duty engine - Bo Li; Wei Tan; Yunpeng Wei; Liyun Fan; Yang Wang; Xianyin Leng; Ge Xiao; Wuqiang Long (Fuel, 2025)

A hybrid Eulerian-Lagrangian Vlasov method for nonlinear wave-particle interaction in weakly inhomogeneous magnetic field - Jiangshan Zheng; Ge Wang; Bo Li (Computer Physics Communications, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

Enhanced digital twin framework for real-time prediction of fatigue damage on semi-submersible platforms under long-term multi-sea conditions - Haiyang Ge; Bo Wu; Xin Li; Qiangqiang Wei; Yunlong Jiang (Ocean Engineering, 2024)

High-affinity potassium transporter TaHAK1 implicates in cesium tolerance and phytoremediation - Jin Liu; Shuai-Bo Chen; Ze-Hua Fan; Haitao Liu; Yinglong Chen; Chandra Shekhar Seth; Evgenios Agathokleous; Tian-Cai Guo; Guo-Zhang Kang; Ge-Zi Li (Journal of Hazardous Materials, 2024)

Response of gut microbiota, antioxidation, and disease resistance to Pacific shrimp fed distiller’s dried grains with solubles replaced soybean meal - Mpwaga Alatwinusa Yohana; Gyan Watson Ray; Yang Qihui; Kou Shiyu; Beiping Tan; Jiahua Wu; Minling Mao; Zhan bo GE; Lan Feng (Aquaculture International, 2024)

GB-SAR geocoding considering the radar attitude inclination angles for building facade deformation extraction - Peng Wang; Licheng Ge; Bin Zhang; Bo Shi; Hang Duan; Chuanfang Ke (International Journal of Remote Sensing, 2024)

Ionized copolyesters with pH-responsive degradability: Accelerated degradation in specific environments - Xiao Li; Wei-Zhen Zheng; Peng-Yuan Xu; Ze-Yang Zhang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Jun-Hui Ji; Ge-Xia Wang (Science of The Total Environment, 2024)

Potassium persulfate enhances humification of chicken manure and straw composting: The perspective of rare and abundant microbial community structure and ecological interactions - Xiujun Tu; Bo Yin; Jie Kang; Zhenchao Wu; Yuhao Guo; Guoxu Ao; Yangcun Sun; Jingping Ge; Wenxiang Ping (Science of The Total Environment, 2024)

Characteristics of soil salinity and water-salt transport in the vadose zone of salt-impacted regions with variable permeability - Zhiyuan Ma; Yanyan Ge; Bo Pang; Wei Liang; Tuerhong Ruze (Environmental Geochemistry and Health, 2024)

Concurrent nitrogen and phosphorus enrichment increases ecosystem carbon use efficiency in an alpine grassland - Wenyu Li; Yunlong He; Ruonan Shen; Ge Hou; Zhoutao Zheng; Bo Zhao; Jiahe Zheng; Qianxin Jiang; Xianzhou Zhang; Yangjian Zhang; Juntao Zhu (Agriculture, Ecosystems & Environment, 2024)

Sustainable recycling of the biodegradable polyester poly(butylene succinate) via selective catalytic hydrolysis and repolymerization - Wei-Zhen Zheng; Xiao Li; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Jun-Hui Ji; Ge-Xia Wang (Resources, Conservation and Recycling, 2024)

Water-soluble biodegradable polyesters with pH and ionic responsivity - Xiao Li; Wei-Zhen Zheng; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Yang Zhao; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2024)

Effect of artificially induced microcracks near the rock surface on granite fragmentation performance under heating treatment - Yanliang Li; Jiming Li; Jianming Peng; Dong Ge; Kun Bo (International Journal of Rock Mechanics and Mining Sciences, 2024)

Local defect structure design enhanced energy storage performance in lead-free antiferroelectric ceramics - Peixuan Li; Simin Wang; Jin Qian; Guanglong Ge; Luomeng Tang; Jinfeng Lin; Weiwei Yang; Jimin Lin; Weikang Lin; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

MicroRNA-specific therapeutic targets and biomarkers of apoptosis following myocardial ischemia–reperfusion injury - Teng Ge; Bo Ning; Yongqing Wu; Xiaolin Chen; Hongfei Qi; Haifang Wang; Mingjun Zhao (Molecular and Cellular Biochemistry, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Directional electron transport and strong chloridion repulsion enabled by Hierarchical NiCo2O4/NiCoP heterojunction for efficient seawater oxidation - Yi-Peng Dong; Jiang-Bo Chen; Jie Ying; Yu-Xuan Xiao; Yuan Tian; Ling Shen; Lei Xia; Ge Tian; Si-Ming Wu; Yi Lu; Xiao-Yu Yang (Chemical Engineering Journal, 2024)

Bismuth oxychloride-sodium alginate hydrogel derived interface desalination solar evaporator for environmental remediation - Xiuling Li; Yangyang Peng; Yanan Pang; Bo Ge; Limin Zhao; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Chemical Engineering Journal, 2024)

Causes and dynamic change characteristics of the 2022 devastating floods in Pakistan - Huayong Chen; Jiang Xiong; Peng Cui; Xiaoqing Chen; Yonggang Ge; Congxi Fang; Bo Zhang; Tao Yang; Inamullah Khan (Natural Hazards, 2024)

Evaluation of fengyun geosynchronous orbit and GPM satellites precipitation products over the southeastern Tibetan plateau - Yunfan Song; Tao Du; Bo Zeng; Qing Wu; Ge Wang (International Journal of Remote Sensing, 2024)

Integrating habitat risk and landscape resilience in forest protection and restoration planning for biodiversity conservation - Chuandong Tan; Bo Xu; Ge Hong; Xuefei Wu (Landscape and Urban Planning, 2024)

Economic life evaluation of reservoir dams based on comprehensive costs and benefits analysis considering potential dam breach: A case study of the Luhun reservoir in China - Wei Ge; Heqiang Sun; Laihong Jing; Zongkun Li; Yongchuang Li; Bo Cao; Te Wang; Yutie Jiao; Hua Zhang; Jianyou Wang; Pieter van Gelder (Journal of Hydrology, 2024)

Comparative study of organic removal by pre-adsorption oxidation and synchronous adsorption oxidation processes: Performance and mechanism - Bo Tan; Ge Gou; Yi Ren; Zhuoyao Fang; Chao Liu; Bo Lai; Naiwen Li; Jun Li (Journal of Hazardous Materials, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Dual-functional TFNC polyester membranes utilizing maltitol for dye/salt separation and desalination - Tonghui Zhang; Yumeng Wang; Bo Ge; Shuangshuang Wang; Yanhu Zhan; Xuefen Wang (Journal of Water Process Engineering, 2024)

Protective effects of butyric acid during heat stress on the survival, immune response, histopathology, and gene expression in the hepatopancreas of juvenile pacific shrimp (L. Vannamei) - Mpwaga Alatwinusa Yohana; Gyan Watson Ray; Qihui Yang; Shiyu Kou; Beiping Tan; Jiahua Wu; Minling Mao; Zhan bo Ge; Lan Feng (Fish & Shellfish Immunology, 2024)

Toward soil carbon storage: The influence of parent material and vegetation on profile-scale microbial community structure and necromass accumulation - Yu-Zhu Li; Xue-Lian Bao; Shi-Xin Tang; Ke-Qing Xiao; Cheng-Jun Ge; Hong-Tu Xie; Hong-Bo He; Carsten W. Mueller; Chao Liang (Soil Biology and Biochemistry, 2024)

Parent material influences soil properties to shape bacterial community assembly processes, diversity, and enzyme-related functions - Yu-Zhu Li; Xue-Lian Bao; Xue-Feng Zhu; Fang-Bo Deng; Ya-Li Yang; Yue Zhao; Hong-Tu Xie; Shi-Xin Tang; Cheng-Jun Ge; Chao Liang (Science of The Total Environment, 2024)

A four-dimensional digital twin framework for fatigue damage assessment of semi-submersible platforms and practical application - Bo Wu; Qiangqiang Wei; Xin Li; Yufeng Kou; Wenyue Lu; Haiyang Ge; Xiaozhou Guo (Ocean Engineering, 2024)

Study on transferring the refrigeration power in the temperature-distributed regenerative refrigeration cycle - Qiang Cao; Pengcheng Wang; Zhiping Wang; Miaomiao Wang; Yuji Chen; Lichun Ge; Peng Li; Qinyu Zhao; Bo Wang; Zhihua Gan (International Journal of Refrigeration, 2024)

The potential ability of fungi in preventing cadmium accumulation in wheat seedlings grown in weakly alkaline soils: Evidence from the application of fungicide - Chenghao Ge; Yixuan Wang; Wenyan Ma; Hafiz Adeel Ahmad; Cheng Cheng; Hong-Bo Li; Dongmei Zhou (Applied Soil Ecology, 2024)

SRMA: a dual-branch parallel multi-scale attention network for remote sensing images sea-land segmentation - Ye Zhu; Bo Wang; Qi Liu; Shihan Tan; Shengjie Wang; Wenyi Ge (International Journal of Remote Sensing, 2024)

Green Synthesis of CQDs via the Trunks of Bauhinia purpurea as Fluorescence Probes for Rapid and Accurate Detection of Quinoline Yellow - Ziyang Ge; Haiying Du; Bo Tang; Jie Deng (Journal of Fluorescence, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

A self-floating graphite felt evaporator: Interface wetting control and its application in environmental remediation and desalination - Zekun Zhang; Yujiao Luo; Mingyang Li; Bo Ge; Limin Zhao; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Chemical Engineering Journal, 2024)

Macroencapsulated Al-Si phase change materials for high temperature latent thermal energy storage - Yunqi Guo; Bo Zhao; Haonan Guo; Yunfei Ge; Nan Sheng; Elisabetta Gariboldi; Chunyu Zhu (Chemical Engineering Journal, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Role of Brain-Derived Neurotrophic Factor in Anxiety or Depression After Percutaneous Coronary Intervention - Bo Ning; Teng Ge; Yongqing Wu; Yuting Wang; Mingjun Zhao (Molecular Neurobiology, 2024)

Vitamin C Alleviates Intestinal Inflammation Caused by Aeromonas hydrophila in Juvenile Blunt Snout Bream (Megalobrama amblycephala) - Abdullateef Mukhtar Muhammad; Chang Yang; Jingyuan Wang; Xianping Ge; Bo Liu; Linghong Miao; Guodong Gao; Qunlan Zhou (Fishes, 2024)
Vitamin C (VC) can be used to increase disease resistance in practice in intensive aquaculture. But it is still unconfirmed whether VC could alleviate inflammation and what dosage is suitable. This study investigated the effects of dietary VC on the immunity and enteritis of juvenile blunt snout bream (Megalobrama amblycephala) challenged with Aeromonas hydrophila. The fish were fed with VC levels ranging from 25.35 to 2231.98 mg/kg for 60 days. After that, fish fed with 150.65 mg/kg, 573.79 mg/kg, and 2231.98 mg/kg VC were challenged with A. hydrophila orally to simulate enteritis. The results showed that 285.39 and 573.79 mg/kg dietary VC significant improved growth performance and feed utilization. Dietary VC (573.79 and 1133.79 mg/kg) significantly enhanced the serum immune parameters, antioxidant enzymes’ activities, and relative gene expressions of ikbα and cat in the liver in the 60-day feeding trail. The survival rate was significantly higher in 573.79 mg/kg dietary VC group than the other two treatments. Cytokines were activated after the bacteria challenge. Dietary 573.79 mg/kg VC caused significantly higher TNF-α level at 12 hpi and maintained a high level of IL-8 at 48 to 72 h compared to other treatments. In conclusion, more than 500 mg/kg VC was needed to maintain the health of blunt snout bream juveniles. Suitable VC would activate cytokines to increase disease resistance along with antioxidant enzymes.

Generation estimation and critical metals quantity assessment of retired mobile phones in Japan - Ang Li; Bo Li; Ge Yang; Kronnaphat Khumvongsa; Jingjin Pan; Xiaolong Song; Xuyang Lei; Suxia Hou; Dong Yang; Bin Lu (Journal of Cleaner Production, 2024)

Over-expansion cycle as clean combustion strategy applied to a marine low-speed dual fuel engine - Jianlin Cao; Yang Wang; Dongsheng Dong; Fuxing Wei; Heng Zhang; Longlong Jiang; Pengbo Dong; Bo Li; Ge Xiao; Wuqiang Long (Journal of Cleaner Production, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Machine learning revealing key factors influencing HONO chemistry in Beijing during heating and non-heating periods - Wenqian Zhang; Shengrui Tong; Siqi Hou; Pusheng Zhao; Yuepeng Pan; Lili Wang; Mengtian Cheng; Dongsheng Ji; Guiqian Tang; Bo Hu; Xin Li; Maofa Ge (Atmospheric Research, 2024)

Pilot test and consolidation theory of marine dredged slurry using the membrane-free horizontal-vacuum method - Yang Zhou; Bo Yin; Peng Wang; Xueyan Ge; Boyi Zhao (Ocean Engineering, 2024)

Epidermal growth factor: Expression in goat endometrial epithelia during early pregnancy and regulation by interferon tau and FOXO1 - Bo Wang; Meng-Die Li; Hai-Yue Xu; Xin-Cheng Zhang; Li-Ge Bu; Ting-Yue Li; Ya Sun; Hua Ni (Animal Reproduction Science, 2024)

Insight into the enhancement effect of humic acid on microbial degradation of triclosan in anaerobic sediments - Juan Chen; Bo Zhang; Chao Wang; Peifang Wang; Ge Cui; Han Gao; Bingbing Feng; Jingjing Zhang (Journal of Hazardous Materials, 2024)

Kinetic and mechanism of the reaction between Cl and several mono-methyl branched alkanes - Yan Chen; Weigang Wang; Junling Li; Li Zhou; Bo Shi; Cici Fan; Ke Wang; Hao Zhang; Hong Li; Maofa Ge (Journal of Environmental Sciences, 2024)

Hierarchical and networked analysis of resilience factors in mountain communities in Southwest China - Yun-fei Zhao; Jian-min Cai; Lan Tang; Hai-bo Li; Shi-yu Hu; Hui-ge Xing (Natural Hazards, 2024)

Griseofulvin enantiomers and bromine-containing griseofulvin derivatives with antifungal activity produced by the mangrove endophytic fungus Nigrospora sp. QQYB1 - Ge Zou; Wencong Yang; Tao Chen; Zhaoming Liu; Yan Chen; Taobo Li; Gulab Said; Bing Sun; Bo Wang; Zhigang She (Marine Life Science & Technology, 2023)

A comprehensive observation on the pollution characteristics of peroxyacetyl nitrate (PAN) in Beijing, China - Hailiang Zhang; Shengrui Tong; Wenqian Zhang; Yanyong Xu; Mingzhu Zhai; Yucong Guo; Xin Li; Lili Wang; Guiqian Tang; Zirui Liu; Bo Hu; Chengtang Liu; et al. (Science of The Total Environment, 2023)

Investigation on jet controlled diffusion combustion (JCDC) mode applied on a marine large-bore two-stroke engine - Jianlin Cao; Dongsheng Dong; Fuxing Wei; Wuqiang Long; Ge Xiao; Longlong Jiang; Bo Li; Yang Wang (Journal of Cleaner Production, 2023)

All-natural environmentally degradable poly (butylene terephthalate-co-caprolactone): A theoretical and experimental study of its degradation properties and mechanisms - Peng-Yuan Xu; Ping-Li Wang; Tian-Yuan Liu; Zhi-Chao Zhen; Bo Lu; Dan Huang; Ge-Xia Wang; Jun-Hui Ji (Science of The Total Environment, 2023)

Efficient production of biosurfactant surfactin by a newly isolated Bacillus subtilis (sp.) 50499 strain from oil-contaminated soil - Yulu Du; Yue Wang; Tianyou Cui; Lianpeng Ge; Fan Yu; Mengqian Zhao; Qihang Xu; Mingjie Jin; Bo Chen; Xuwei Long (Food and Bioproducts Processing, 2023)

Chemical functionalization of commercial Pt/C electrocatalyst towards formic acid electrooxidation - Zi-Xin Ge; Bo-Qiang Miao; Xin-Long Tian; Bin He; Yu Chen (Chemical Engineering Journal, 2023)

The influence of spermidine on the build-up of fucoxanthin in Isochrysis sp. Acclimated to varying light intensities - Yahui Bo; Shanshan Wang; Feifei Ma; Artem Yurevich Manyakhin; Guilin Zhang; Xiaohui Li; Chengxu Zhou; Baosheng Ge; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

Machine learning reveals the effects of drivers on PM2.5 and CO2 based on ensemble source apportionment method - Han Xu; Yi Ge; Chun Zhang; Zhenyu Wang; Bo Xu; Huan Zhao; Junbo Huang; Gen Wang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Research, 2023)

Ferroptosis-Related Immune Genes in Hematological Diagnosis of Parkinson’s Diseases - Heyue Lu; Bo Zhang; Tingting Yin; Ye Hua; Chenyang Cao; Min Ge; Dandan Shen; You Lang Zhou; Zhongzheng Jia (Molecular Neurobiology, 2023)

Rutin hydrate relieves neuroinflammation in zebrafish models: Involvement of NF-κB pathway as a central network - Ying Hu; Kun Jia; Yatong Zhou; Lixin Chen; Fei Wang; Xiaokun Yi; Yong Huang; Yurui Ge; Xiaomei Chen; Dalong Liao; Yuyang Peng; Yunlong Meng; et al. (Fish & Shellfish Immunology, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

Cascade signal amplification strategy by coupling chemical redox-cycling and Fenton-like reaction: Toward an ultrasensitive split-type fluorescent immunoassay - Lin-Ge Chen; Lu Sun; Ning-Ning Wu; Bei-Bei Tao; Hai-Bo Wang (Analytica Chimica Acta, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Use of food attractants to monitor and forecast Spodoptera frugiperda (J. E. Smith) seasonal abundance in southern China - Wei He; Liying Wang; Chunyang Lv; Shishuai Ge; Haowen Zhang; Shan Jiang; Bo Chu; Xianming Yang; Kris A. G. Wyckhuys; Kongming Wu (Journal of Pest Science, 2023)

Bamboo Plantation Establishment Changes Rainfall Partitioning and Chemistry - Tao Yang; Yong Li; Xueying Ouyang; Bo Wang; Xiaomin Ge; Luozhong Tang (Ecosystems, 2023)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Reconstructing post-mid Pleistocene glacial-dammed paleolakes in the Tsangpo Gorge, southeastern Tibetan Plateau - Ping Wang; Huiying Wang; Gang Hu; Yukui Ge; Tao Liu; Bo Xu (Quaternary Science Reviews, 2023)

Remote sensing for landslide investigations: A progress report from China - Qiang Xu; Bo Zhao; Keren Dai; Xiujun Dong; Weile Li; Xing Zhu; Yinghui Yang; Xianxuan Xiao; Xin Wang; Jian Huang; Huiyan Lu; Bo Deng; et al. (Engineering Geology, 2023)

Efficient depolymerization of alkali lignin to monophenols using one-step synthesized Cu–Ni bimetallic catalysts inlaid in homologous biochar - Jiubing Zhang; Bo Chen; Yuanyuan Ge; Zhili Li (Biomass and Bioenergy, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Role of TPEN in Amyloid-β25–35-Induced Neuronal Damage Correlating with Recovery of Intracellular Zn2+ and Intracellular Ca2+ Overloading - Wen-bo Chen; Yu-xiang Wang; Hong-gang Wang; Di An; Dan Sun; Pan Li; Tao Zhang; Wan-ge Lu; Yan-qiang Liu (Molecular Neurobiology, 2023)

Understanding the effects of tree-crop intercropping systems on crop production in China by combining field experiments with a meta-analysis - Tao Yang; Xueying Ouyang; Bo Wang; Di Tian; Cheng Xu; Zeyang Lin; Xiaomin Ge; Luozhong Tang (Agricultural Systems, 2023)

Coupling activation and curing to tune the permselectivity of poly(piperazine amide) nanofiltration membranes - Dongsheng Zhao; Jiyu Song; Yiwen Zhang; Zhiquan Lin; Bo He; Nanfu Qiao; Kangping Huang; Wei Zhang; Shuang Ge; Yuying Li; B. Larry Li; Kang Xie; et al. (Journal of Water Process Engineering, 2023)

Fluorescence tracing the degradation process of biodegradable PBAT: Visualization and high sensitivity - Tian-Yuan Liu; Zhi-Chao Zhen; Xiao-Ling Zang; Peng-Yuan Xu; Ge-Xia Wang; Bo Lu; Fei Li; Ping-Li Wang; Dan Huang; Jun-Hui Ji (Journal of Hazardous Materials, 2023)

Constructing dendrite suppressing mixed sulfide solid electrolyte for high-rate lithium metal batteries - Zeyu Ge; Nanshan Chen; Rui Wang; Rui Ma; Bo Fan; David Le coq; Xianghua Zhang; Hongli Ma; Bai Xue (Chemical Engineering Journal, 2023)

Discovery of seven-membered ring berberine analogues as highly potent and specific hCES2A inhibitors - Yun Yang; Yuan Xiong; Guanghao Zhu; Mengru Sun; Kun Zou; Yitian Zhao; Yong Zhang; Zhijian Xu; Yiming Li; Weiliang Zhu; Qi Jia; Bo Li; et al. (Chemico-Biological Interactions, 2023)

A framework for identifying the onset of landslide acceleration based on the exponential moving average (EMA) - Jia-zhu Wang; Neng-pan Ju; Yong-bo Tie; Yong-jian Bai; Hua Ge (Journal of Mountain Science, 2023)

Active pollination in a functionally dioecious Ficus species: An interplay between pollinator behaviour and floral morphology - Bai-Ge Miao; Ming-Xin Liu; Bo Wang; Yan-Qiong Peng; Annick Lesne; Finn Kjellberg; K．Charlotte Jandér (Flora, 2023)

Highly enhanced energy storage performance of trilayered gradient polymer-based nanocomposite via 2D SNO@Ag nanosheets - Hairui Bai; Guanglong Ge; Fei Yan; Kun Zhu; Jin Qian; Cheng Shi; Yanxia Li; Haijiao Xie; Bo Shen; Jiwei Zhai (Chemical Engineering Journal, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

Dispersed cobalt embedded nitrogen-rich carbon framework activates peroxymonosulfate for carbamazepine degradation: cobalt leaching restriction and mechanism investigation - Yuesen Wang; Yanchun Huang; Ge Gou; Naiwen Li; Longguo Li; Yuxin He; Chao Liu; Bo Lai; Hailong Sun (Chemosphere, 2023)

On-site determination of water toxicity based on freeze-dried electrochemically active bacteria - Yuxuan Zang; Bo Cao; Hongyu Zhao; Beizhen Xie; Yanhong Ge; Yue Yi; Hong Liu (Science of The Total Environment, 2023)

A Cre knockin mouse reveals specific expression of Agouti gene in mesenchymal lineage cells in multiple organs and provides a unique tool for conditional gene targeting - Xing-Ru Shen; He-Li Zhang; Xu-Bo Zhao; Yang-Ge Wang; Xiao-Yang Tan; Lipeng Gao; Ruilin Sun; Xin-Hua Liao (Transgenic Research, 2023)

Inhibitory effect of volatile organic compounds from Bacillus flexus TR-1 against Aspergillus flavus and aflatoxins in grains during storage - An-Dong Gong; Meng-Ge Song; Hua-Ling Wang; Gao-Zhan Wang; Jian-Hua Wang; Jing-Bo Zhang (BioControl, 2023)

The essentiality of dietary myo-inositol to oriental river prawn (Macrobrachium nipponense): Evidence in growth performance, lipid metabolism and mitochondrial function - Ming-Yang Liu; Miao Sun; Ling Zhang; Ya-Ping Ge; Bo Liu; Xiang-Fei Li (Aquaculture, 2023)

Enhanced degradation of poly(ethylene terephthalate) by the addition of lactic acid / glycolic acid: composting degradation, seawater degradation behavior and comparison of degradation mechanism - Tian-Yuan Liu; Peng-Yuan Xu; Dan Huang; Bo Lu; Zhi-Chao Zhen; Wei-Zhen Zheng; Yan-Chao Dong; Xiao Li; Ge-Xia Wang; Jun-Hui Ji (Journal of Hazardous Materials, 2023)

Morphology evolution regulation of dual-doped S, Fe-NiMoO4 microrods based on precipitation-dissolution equilibrium for oxygen evolution - Meng-Xuan Li; Bo Xiao; Zi-Yi Zhao; Yu Ma; Ya-Nan Zhou; Xin-Yu Zhang; Feng-Ge Wang; Yong-Ming Chai; Bin Dong (Fuel, 2023)

Response characteristics of antibiotic resistance genes and bacterial communities during agricultural waste composting: Focusing on biogas residue combined with biochar amendments - Yuewei He; Xiaowei Yin; Fanghong Li; Bo Wu; Ling Zhu; Dabing Ge; Nanyi Wang; Anwei Chen; Lihua Zhang; Binghua Yan; Hongli Huang; Lin Luo; et al. (Bioresource Technology, 2023)

Trace elements in outdoor and indoor PM2.5 in urban schools in Xi’an, Western China: characteristics, sources identification and health risk assessment - Runyu Wang; Xinxin Ding; Jingzhi Wang; Zhibao Dong; Hongmei Xu; Ge Ma; Bo Gao; Han Song; Menghan Yang; Junji Cao (Environmental Geochemistry and Health, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Multiple-objective optimization of Jet Controlled Compression Ignition (JCCI) mode with dual-direct injection in a high-speed light-duty engine - Bo Li; Jian Wang; Heng Zhang; Liyun Fan; Xianyin Leng; Wuqiang Long; Ge Xiao (Fuel, 2023)

Naive Bayes classification-based surface water gap-filling from partially contaminated optical remote sensing image - Bingxin Bai; Yumin Tan; Gennadii Donchyts; Arjen Haag; Bo Xu; Ge Chen; Albrecht H. Weerts (Journal of Hydrology, 2023)

Atmospheric chemistry of nitrous acid and its effects on hydroxyl radical and ozone at the urban area of Beijing in early spring 2021 - Wenqian Zhang; Shengrui Tong; Deng Lin; Fangjie Li; Xinran Zhang; Lili Wang; Dongsheng Ji; Guiqian Tang; Zirui Liu; Bo Hu; Maofa Ge (Environmental Pollution, 2023)

Insight into different adsorption behaviors of two fluoroquinolone antibiotics by sediment aggregation fractions - Bo Zhang; Juan Chen; Chao Wang; Peifang Wang; Ge Cui; Jingjing Zhang; Yu Hu; Han Gao (Environmental Science and Pollution Research, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

Two new alkaloids from Tibetan medicine of Hypecoum leptocarpum - Bo Sun; Israa Assani; Chun-Gu Wang; Mu-Xuan Wang; Ling-Fei Liu; Yan Li; Ge Yan; Yun-Ruo Yang; Zhi Chen; Zhi-Xin Liao (Natural Product Research, 2022)

Two new chemical constituents from Lonicera japonica - Jian-liang Geng; Hai-bo Li; Wen-jun Liu; Zhen-zhong Wang; Wen Ge; Wei Xiao (Natural Product Research, 2022)

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

Numerical Simulation Study of the Horizontal Submerged Jet Based on the Wray–Agarwal Turbulence Model - Bo Hu; Chuan Wang; Hui Wang; Qian Yu; Jinhua Liu; Yong Zhu; Jie Ge; Xinxin Chen; Yang Yang (Journal of Marine Science and Engineering, 2022)
The horizontal submerged jet (HSJ), as a special form of jet, is widely used in aerospace, food and drug, water engineering, and other industries. In order to further understand the mechanism of the HSJ, the Wray–Agarwal turbulence model was used to predict the HSJ with different incidence heights H/D and Reynolds number (Re) conditions in this paper. The results show that the jet horizontal height H/D has a large influence on the flow field structure. The unsteady flow within the flow field is dominated by vortexes. In addition, their distribution is relatively independent of H/D. Under different H/D conditions, the axial velocity distribution of the jet has very high similarity, all of them have an obvious velocity inflection point at x = 10D. When H/D is small, the wall attachment effect of the jet and the boundary layer effect generated at the bottom of the fluid domain have a certain role in maintaining the velocity of the jet near the wall, resulting in a significantly higher axial velocity than other H/D conditions, up to 1.29 times. In this paper, we thoroughly investigated the structure of the internal flow field and velocity distribution of the submerged horizontal jet. The results have a guiding significance for engineering practice and academic research.

Versatile superhydrophobic bismuth molybdate cotton fabric for oil/water separation and decompose dyestuff - Jie Yue; Shaowang Tang; Bo Ge; Min Wang; Guina Ren; Xin Shao (Environmental Science and Pollution Research, 2022)

Flow Characteristics of Oblique Submerged Impinging Jet at Various Impinging Heights - Di Zhang; Hongliang Wang; Jinhua Liu; Chuan Wang; Jie Ge; Yong Zhu; Xinxin Chen; Bo Hu (Journal of Marine Science and Engineering, 2022)
To study the influence of impinging height H/D on the flow field characteristics of oblique submerged impinging jets, the numerical calculation of an oblique submerged impinging jet was carried out based on Wray–Agarwal (W–A) turbulence model. The jet flow field structure and pressure distribution under various impinging heights (1 ≤ H/D ≤ 8) when the impinging angle was θ = 45° were analyzed. The results show that with the increase in the impinging height, the diffusion degree of the jet gradually increased and the velocity decreased when the jet reached the impingement region, and the distance between the stagnation point (SP) and the geometric center (GC) gradually increased, the flow angle φ along the jet centerline remained constant in the free-jet region and rapidly decreased in the impingement region. The impingement plate pressure distribution at various heights was similar, and the impinging pressure concentration on the upstream side of the maximum pressure point was higher.

The role of currently used medicinal plants in aquaculture and their action mechanisms: A review - Dawit Adisu Tadese; Changyou Song; Cunxin Sun; Bo Liu; Bo Liu; Qunlan Zhou; Pao Xu; Xianping Ge; Mingyang Liu; Xiaodi Xu; Metekia Tamiru; Zhigang Zhou; et al. (Reviews in Aquaculture, 2022)
Global aquaculture development increased rapidly in recent years, and the sector has become one of the fastest‐growing industries in the animal‐derived food production system. However, disease outbreak remains a major challenge that hinders sustainable production through an advanced level of intensification. Recently, antibiotics applied have been restricted globally against aquatic disease outbreaks due to their apparent accumulation in the tissues, which imposes on the development of resistant bacteria. Naturally available medicinal plants were tested to combat some pathogens affecting humans and animals, as they contain a wide range of active substances that can induce biological functions. Currently, medicinal plants are being tested in aquaculture as a safe and eco‐friendly substance to modulate immune status, enhance growth performance and prevent fish disease. Moreover, different parts (e.g. leaf, flower and rhizome) and forms (e.g. crude, extract and active ingredient) of plants are used to modulate specific biological functions (e.g. growth promoter, anti‐stress, immunostimulants, appetite stimulation, antibacteria, anti‐parasite and anti‐virus). Medicinal plants are also used to defend the aquaculture animal from external stressors, such as poor water quality, high environmental temperature and overcrowding. This paper aims to provide information on the role of currently used medicinal plants on aquaculture animals and their action mechanisms. In conclusion, the current review suggested that the utilisation of medicinal plants remained untapped in uncovering the biological activities of active substances against a variety of diseases across diverse species of aquaculture animals.

A Numerical Study of a Submerged Water Jet Impinging on a Stationary Wall - Bo Hu; Hui Wang; Jinhua Liu; Yong Zhu; Chuan Wang; Jie Ge; Yingchong Zhang (Journal of Marine Science and Engineering, 2022)
The impinging jet is a classical flow model with relatively simple geometric boundary conditions, and it is widely used in marine engineering. In recent years, scholars have conducted more and more fundamental studies on impact jets, but most of the classical turbulence models are used in numerical simulations, and the accuracy of their calculation results is still a problem in regions with large changes in velocity gradients such as the impact zone. In order to study the complex flow characteristics of the water flow under the condition of a submerged jet impacting a stationary wall, the Wray–Agarwal turbulence model was chosen for the Computational Fluid Dynamics (CFD) numerical simulation study of the impacting jet. Continuous jets with different Reynolds numbers and different impact heights H/D were used to impact the stationary wall, and the results show that the jet flow structure depends on the impact height and is relatively independent of the Reynolds number. With the increase in the impact height, the diffusion of the jet reaching the impact area gradually increases, and its velocity gradually decreases. As the impact height increases, the maximum pressure coefficient decreases and the rate of decrease increases gradually, and the dimensionless pressure distribution is almost constant. In this paper, the flow field structure and pressure characteristics of a continuous submerged jet impacting a stationary wall are explored in depth, which is of great guidance to engineering practice.

A Physics-Informed Neural Network for the Prediction of Unmanned Surface Vehicle Dynamics - Peng-Fei Xu; Chen-Bo Han; Hong-Xia Cheng; Chen Cheng; Tong Ge (Journal of Marine Science and Engineering, 2022)
A three-degrees-of-freedom model, including surge, sway and yaw motion, with differential thrusters is proposed to describe unmanned surface vehicle (USV) dynamics in this study. The experiment is carried out in the Qing Huai River and the data obtained from different zigzag trajectories are filtered by a Gaussian filtering method. A physics-informed neural network (PINN) is proposed to identify the dynamic models of the USV. PINNs combine the advantages of data-driven machine learning and physical models. They can also embed the speed and steering models into the loss function, which can significantly retain all types of information. Compared with traditional neural networks, the results show that the PINN has better generalization ability in predicting the surge and sway velocities and rotation speed with only limited training data.

Comparative assessments between conventional and promising technologies for wheat aging or mold detection - Yue-hong Gong; Tie-jun Yang; Yi-tao Liang; Hong-yi Ge; Er-bo Shen (Cereal Research Communications, 2021)

Understanding the Yanshan volcano eruption in the Chaihe–Arxan volcanic field, northeastern China - Xiao-ge Cui; Jian-dong Xu; Hong-mei Yu; Bo Zhao; Wen-jian Yang (Arabian Journal of Geosciences, 2021)

Forging or casting: new evidence of iron production in the Chengdu Plain in the Han dynasty - Mengyi Zhang; Linjie Ge; Tian Qiu; Qianqian Gan; Bo Yang; Yuniu Li (Archaeological and Anthropological Sciences, 2021)

Study on the Effect and Mechanism of Water Immersion on the Characteristic Temperature during Coal Low-Temperature Oxidation - Xiaowei Zhai; Bobo Song; Bo Wang; Teng Ma; Hui Ge (Natural Resources Research, 2021)

Pollution risk assessment of heavy metals in the sediments of upstream Hanjiang River, China - Fengmin Song; Hong-Guang Ge; Hangang Zhao; Zhifeng Liu; Juan Si; Bo Tang (Earth Science Informatics, 2021)

HSV-1 H129-Derived Anterograde Neural Circuit Tracers: Improvements, Production, and Applications - Hong Yang; Feng Xiong; Yi-Ge Song; Hai-Fei Jiang; Hai-Bin Qin; Jing Zhou; Sha Lu; Steven F. Grieco; Xiangmin Xu; Wen-Bo Zeng; Fei Zhao; Min-Hua Luo (Neuroscience Bulletin, 2021)

Geometric model for toppling-prone deformation of layered reverse-dip slope - Liangfu Xie; Ying Ge; Jiaqi Zhang; Shunli Tan; Bo Wang; Echuan Yan; Yongjun Qin; Jianhu Wang; Chen Shi; Guangming Yu (Natural Hazards, 2021)

Molecular cloning and functional characterization of the hypoxia-inducible factor-1α in bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Bo Liu; Bing-Wen Xi; Liang-Kun Pan; Xian-Ping Ge (Fish Physiology and Biochemistry, 2021)

Environment dependent microbial co‐occurrences across a cyanobacterial bloom in a freshwater lake - Gang Wu; Leixin Ge; Na Zhao; Fei Liu; Zunji Shi; Ningning Zheng; Dan Zhou; Xingpeng Jiang; Larry Halverson; Bo Xie (Environmental Microbiology, 2021)
Summary Microbial taxon–taxon co‐occurrences may directly or indirectly reflect the potential relationships between the members within a microbial community. However, to what extent and the specificity by which these co‐occurrences are influenced by environmental factors remains unclear. In this report, we evaluated how the dynamics of microbial taxon–taxon co‐occurrence is associated with the changes of environmental factors in Nan Lake at Wuhan city, China with a Modified Liquid Association method. We were able to detect more than 1000 taxon–taxon co‐occurrences highly correlated with one or more environmental factors across a phytoplankton bloom using 16S rRNA gene amplicon community profiles. These co‐occurrences, referred to as e nvironment d ependent co‐occurrences (ED_co‐occurrences), delineate a unique network in which a taxon–taxon pair exhibits specific, and potentially dynamic correlations with an environmental parameter, while the individual relative abundance of each may not. Microcystis involved ED_co‐occurrences are in important topological positions in the network, suggesting relationships between the bloom dominant species and other taxa could play a role in the interplay of microbial community and environment across various bloom stages. Our results may broaden our understanding of the response of a microbial community to the environment, particularly at the level of microbe–microbe associations.

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Slope structures and formation of rock-soil aggregate landslides in deeply incised valleys - Yong-jian Bai; Yun-sheng Wang; Hua Ge; Yong-bo Tie (Journal of Mountain Science, 2020)

Metformin prevents against oxidative stress-induced senescence in human periodontal ligament cells - Yunchun Kuang; Bo Hu; Ge Feng; Mingli Xiang; Yuejia Deng; Minmin Tan; Jie Li; Jinlin Song (Biogerontology, 2020)

3D-Printed Wearable Personalized Orthodontic Retainers for Sustained Release of Clonidine Hydrochloride - Heliu Jiang; Junhui Fu; Mingguang Li; Shanshan Wang; Bo Zhuang; Haiyan Sun; Cheng Ge; Bin Feng; Yiguang Jin (AAPS PharmSciTech, 2019)

Global trends and future prospects of e-waste research: a bibliometric analysis - Ya Gao; Long Ge; Shuzhen Shi; Yue Sun; Ming Liu; Bo Wang; Yi Shang; Jiarui Wu; Jinhui Tian (Environmental Science and Pollution Research, 2019)

Physiological response of the toxic and non-toxic strains of a bloom-forming cyanobacterium Microcystis aeruginosa to changing ultraviolet radiation regimes - Zhiguang Xu; Guang Gao; Bo Tu; Hongjin Qiao; Hongmei Ge; Hongyan Wu (Hydrobiologia, 2019)

Dietary leucine affects glucose metabolism and lipogenesis involved in TOR/PI3K/Akt signaling pathway for juvenile blunt snout bream Megalobrama amblycephala - Hualiang Liang; Ahmed Mokrani; Hopeson Chisomo-Kasiya; Ke Ji; Xianping Ge; Mingchun Ren; Bo Liu; Bingwen Xi; Ajun Sun (Fish Physiology and Biochemistry, 2019)

Fish assemblage structure in relation to seasonal environmental variation in sub‐lakes of the Poyang Lake floodplain, China - Bin‐Song Jin; Kirk O. Winemiller; Bo Shao; Ji‐Ke Si; Jie‐Feng Jin; Gang Ge (Fisheries Management and Ecology, 2019)
The Yangtze River and its watershed have undergone vast changes resulting from centuries of human impacts, yet ecological knowledge of the system is limited. The seasonal variation and spatial variation of three sub‐lakes of Poyang Lake, a huge wetland in the middle Yangtze Basin, were investigated to examine how fish assemblages respond to seasonal hydrology and associated environmental conditions. In all three sub‐lakes, fish assemblage structure revealed strong variations associated with seasonal water level fluctuation. Fish species richness in all sub‐lakes was highest during the middle of the monsoon season and lowest during the dry season. Fish numerical abundance and biomass varied significantly, with several of the most common species having inconsistent patterns of seasonal variation among sub‐lakes. Fish assemblage structure was significantly associated with environmental gradients defined by water level, aquatic macrophyte coverage, conductivity and dissolved oxygen concentration. Assemblage composition in all three sub‐lakes underwent strongest shifts between December and April, the period when water levels were lowest and fishing has the greatest impact on fish stocks. Future impacts that change the hydrology of the middle Yangtze would alter the dynamics of habitat connectivity and affect environmental conditions and fish assemblages of the Poyang Lake wetland system.

A new dimeric secoiridoids derivative, japonicaside E, from the flower buds of Lonicera japonica - Wen Ge; Hai-Bo Li; Hui Fang; Biao Yang; Wen-Zhe Huang; Wei Xiao; Zhen-Zhong Wang (Natural Product Research, 2019)

The relative abundance of alkane‐degrading bacteria oscillated similarly to a sinusoidal curve in an artificial ecosystem model from oil‐well products - Guoqiang Li; Peike Gao; Bo Zhi; Bing Fu; Ge Gao; Zhaohui Chen; Mengli Gao; Mengmeng Wu; Ting Ma (Environmental Microbiology, 2018)
Summary Microbial phylogenetic diversity and species interactions in natural ecosystems have been investigated extensively, but our knowledge about their ecological roles, community dynamics and succession patterns is far from complete. This knowledge is essential to understand the complicated interactions of microorganisms in natural ecosystems. Here, an artificial ecosystem model of microorganisms was constructed from oil‐well products and cultivated in a chemostat to investigate the succession pattern of alkane‐degrading bacteria, a functional population in oil reservoirs. Their abundance was quantified by an improved qPCR technique. Our results showed that the phylogenetic structure of this artificial ecosystem model is stable during most of the chemostat cultivation process, while the genotype structure of alkane‐degrading bacteria containing alk B genes shifted and their relative abundance oscillated similarly to a sinusoidal curve, like the succession pattern of producers in the Lotka–Volterra model. These results suggest that some theoretical frameworks of macroecology may work well in microbial ecosystems and be an efficient tool to understand them.

Dietary Chromium Picolinate Supplementation Affects Growth, Whole-Body Composition, and Gene Expression Related to Glucose Metabolism and Lipogenesis in Juvenile Blunt Snout Bream, Megalobrama amblycephala - Mingchun Ren; Ahmed Mokrani; Hualiang Liang; Ke Ji; Jun Xie; Xianping Ge; Bo Liu (Biological Trace Element Research, 2018)

Long-term follow-up of the effects of fecal microbiota transplantation in combination with soluble dietary fiber as a therapeutic regimen in slow transit constipation - Xueying Zhang; Hongliang Tian; Lili Gu; Yongzhan Nie; Chao Ding; Xiaolong Ge; Bo Yang; Jianfeng Gong; Ning Li (Science China Life Sciences, 2018)

Study on the Clinical Features and Prognosis of Penicilliosis marneffei Without Human Immunodeficiency Virus Infection - Ying-ge Wang; Jin-mei Cheng; Hai-bo Ding; Xi Lin; Guo-hao Chen; Mei Zhou; Sheng-nan Ye (Mycopathologia, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

Isotope Chronology and Geochemistry of the Lower Carboniferous Granite in Xilinhot, Inner Mongolia, China - Xiaocheng Zhao; Wenxiao Zhou; Dong Fu; Bo Huang; Mengchun Ge (Journal of Earth Science, 2018)

Compounds with inhibitory activity on peristalsis from the seeds of Holarrhena antidysenterica - Hai-Hua Xie; Jian Su; Xiao-Lei Ge; Ting-Ting Dong; Xin Li; Hui-Min Wen; Bo-Hang Sun (Natural Product Research, 2018)

Molecular characterization and recombination analysis of porcine reproductive and respiratory syndrome virus emerged in southwestern China during 2012–2016 - Long Zhou; Runmin Kang; Gaosheng Ji; Yiming Tian; Mengyun Ge; Bo Xie; Xin Yang; Hongning Wang (Virus Genes, 2018)

Native and non-native halophytes resiliency against sea-level rise and saltwater intrusion - Lian Xue; Xiuzhen Li; Zhongzheng Yan; Qian Zhang; Wenhui Ding; Xing Huang; Bo Tian; Zhenming Ge; Qiuxiao Yin (Hydrobiologia, 2018)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

Basic fibroblast growth factor activates β-catenin/RhoA signaling in pulmonary fibroblasts with chronic obstructive pulmonary disease in rats - Zhengxing Ge; Bo Li; Xun Zhou; Yi Yang; Jun Zhang (Molecular and Cellular Biochemistry, 2016)

Effects of Brevibacillus brevis FJAT-1501-BPA on growth performance, faecal microflora, faecal enzyme activities and blood parameters of weaned piglets - Jianmei Che; Shaowen Ye; Bo Liu; Yuanyuan Deng; Qianqian Chen; Cibin Ge; Guohong Liu; Jieping Wang (Antonie van Leeuwenhoek, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Effects of fish meal replacement by soybean peptide on growth performance, digestive enzyme activities, and immune responses of yellow catfish Pelteobagrus fulvidraco - Zhen-xin Zhao; Chang-you Song; Jun Xie; Xian-ping Ge; Bo Liu; Si-lei Xia; Shun Yang; Qing Wang; Sai-hua Zhu (Fisheries Science, 2016)

Growth performance and immune responses of gibel carp, Carassius auratus gibelio, fed with graded level of rare earth-chitosan chelate - Qun-lan Zhou; Jun Xie; Xian-ping Ge; H. Michael Habte-Tsion; Bo Liu; Mingchun Ren (Aquaculture International, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

Gomisin A is a Novel Isoform-Specific Probe for the Selective Sensing of Human Cytochrome P450 3A4 in Liver Microsomes and Living Cells - Jing-Jing Wu; Guang-Bo Ge; Yu-Qi He; Ping Wang; Zi-Ru Dai; Jing Ning; Liang-Hai Hu; Ling Yang (The AAPS Journal, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

Cystatin C is an Independent Risk Factor and Therapeutic Target for Acute Ischemic Stroke - Bo Yang; Jiangtao Zhu; Zhigang Miao; Beiqun Zhou; Wei Ge; Heqing Zhao; Xingshun Xu (Neurotoxicity Research, 2015)

Effect of surfactants on the removal and acute toxicity of aqueous nC60 aggregates in water treatment process - Ling Ge; George Kirumba; Bo Zhang; Amrita Pal; Yiliang He (Environmental Science and Pollution Research, 2015)

Sigma 1 receptor activation regulates brain-derived neurotrophic factor through NR2A-CaMKIV-TORC1 pathway to rescue the impairment of learning and memory induced by brain ischaemia/reperfusion - Qian Xu; Xue-Fei Ji; Tian-Yan Chi; Peng Liu; Ge Jin; Shao-Li Gu; Li-Bo Zou (Psychopharmacology, 2015)

A multiplex RT-PCR for simultaneous detection and identification of five viruses and two viroids infecting chrysanthemum - Xiting Zhao; Xingliang Liu; Beibei Ge; Mingjun Li; Bo Hong (Archives of Virology, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

GPU accelerated marine data visualization method - Bo Li; Ge Chen; Fenglin Tian; Baomin Shao; Pengbo Ji (Journal of Ocean University of China, 2014)

A bZIP transcription factor, LrbZIP1, is involved in Lilium regale Wilson defense responses against Fusarium oxysporum f. sp. lilii - Nannan Zhang; Diqiu Liu; Wei Zheng; Hua He; Bo Ji; Qing Han; Feng Ge; Chaoyin Chen (Genes & Genomics, 2014)

The PR10 gene family is highly expressed in Lilium regale Wilson during Fusarium oxysporum f. sp. lilii infection - Hua He; Diqiu Liu; Nannan Zhang; Wei Zheng; Qing Han; Bo Ji; Feng Ge; Chaoyin Chen (Genes & Genomics, 2014)

C-type natriuretic peptide inhibiting vascular calcification might involve decreasing bone morphogenic protein 2 and osteopontin levels - Jing-Jing Chen; Jing Zhang; Yan Cai; Ye-Bo Zhou; Ge-Bo Wen; Chao-Shu Tang; Yong-Fen Qi; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2014)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

Physiological and biochemical responses of Phoebe bournei seedlings to water stress and recovery - Yongjin Ge; Xiaoyong He; Junfeng Wang; Bo Jiang; Ronghua Ye; Xinchun Lin (Acta Physiologiae Plantarum, 2014)

Xanthoceraside attenuates tau hyperphosphorylation and cognitive deficits in intracerebroventricular-streptozotocin injected rats - Peng Liu; Li-Bo Zou; Li-Hua Wang; Qing Jiao; Tian-Yan Chi; Xue-Fei Ji; Ge Jin (Psychopharmacology, 2014)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Assessment of the ecological security of immobilized enzyme remediation process with biological indicators of soil health - Ying Zhang; Xiaonan Dong; Zhao Jiang; Bo Cao; Shijie Ge; Miao Hu (Environmental Science and Pollution Research, 2013)

Inhibitory effect of curcumin analogs on tissue factor procoagulant activity and their preliminary structure–activity relationships - Hai-Xia Ge; Ling Chen; Jian Zhang; Jun-Ping Kou; Bo-Yang Yu (Medicinal Chemistry Research, 2013)

Cloning and functional analysis of putative malonyl-CoA:acyl-carrier protein transacylase gene from the docosahexaenoic acid-producer Schizochytrium sp. TIO1101 - Rubin Cheng; Yuqing Ge; Bo Yang; Xiaoming Zhong; Xiangzhi Lin; Zhen Huang (World Journal of Microbiology and Biotechnology, 2013)

Design and implementation of a 3D ocean virtual reality and visualization engine - Ge Chen; Bo Li; Fenglin Tian; Pengbo Ji; Wenqing Li (Journal of Ocean University of China, 2012)

Effects of drought stress on phosphorus and potassium uptake dynamics in summer maize (Zea mays) throughout the growth cycle - Ti-Da Ge; Ning-Bo Sun; Li-Ping Bai; Chen-Li Tong; Fang-Gong Sui (Acta Physiologiae Plantarum, 2012)

Current status of percutaneous coronary intervention of chronic total occlusion - Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2012)

Compromised DNA Damage Repair Promotes Genetic Instability of the Genomic Magnetosome Island in Magnetospirillum magneticum AMB-1 - Tao Bo; Kuan Wang; Xin Ge; Guanjun Chen; Weifeng Liu (Current Microbiology, 2012)

Effect of high dietary carbohydrate on growth, serum physiological response, and hepatic heat shock cognate protein 70 expression of the top-mouth culter Erythroculter ilishaeformis Bleeker - Bo Liu; Jun Xie; Xian-ping Ge; Ling-hong Miao; Guangyu Wang (Fisheries Science, 2012)

A meta-analysis of β1-adrenergic receptor gene polymorphisms in idiopathic dilated cardiomyopathy - Bo Jin; Qu-Zhen Ge-Shang; Yong Li; Wei Shen; Hai-Ming Shi; Huan-Chun Ni (Molecular Biology Reports, 2012)

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

Varied association of prothrombin G20210A polymorphism with coronary artery disease susceptibility in different ethnic groups: evidence from 15,041 cases and 21,507 controls - Bo Jin; Yong Li; Qu-Zhen Ge-Shang; Huan-Chun Ni; Hai-Ming Shi; Wei Shen (Molecular Biology Reports, 2011)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

A mutant of infectious Asia 1 serotype foot-and-mouth disease virus with the deletion of 10-amino-acid in the 3A protein - Shuang Li; Mingchun Gao; Runxiang Zhang; Ge Song; Jun Song; Dandan Liu; Yongsheng Cao; Tingting Li; Bo Ma; Xiangtao Liu; Junwei Wang (Virus Genes, 2010)

Microbial community analysis in crab ponds by denaturing gradient gel electrophoresis - Yan Fen Cheng; Qun Lan Zhou; Jun Xie; Xian Ping Ge; Wei-Yun Zhu; Bo Liu (World Journal of Microbiology and Biotechnology, 2010)

Establishment and maintenance of three Chinese human embryonic stem cell lines - Di Zhou; Ge Lin; Chang-Qing Xie; Bo Xiong; Xiao-Ying Zhou; Xiao-Bing Qian; Yi Liao; Guang-Xiu Lu (In Vitro Cellular & Developmental Biology - Animal, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Sanchi ginseng (Panax notoginseng (Burkill) F. H. Chen) in China: distribution, cultivation and variations - Hong Bo Guo; Xiu Ming Cui; Na An; Ge Ping Cai (Genetic Resources and Crop Evolution, 2010)

Interspecific relationships and origins of Taxaceae and Cephalotaxaceae revealed by partitioned Bayesian analyses of chloroplast and nuclear DNA sequences - Da Cheng Hao; Pei Gen Xiao; BeiLi Huang; Guang Bo Ge; Ling Yang (Plant Systematics and Evolution, 2008)

Autophagy is activated and might protect neurons from degeneration after traumatic brain injury - Yan-Bo Zhang; Sheng-Xing Li; Xi-Ping Chen; Li Yang; Yun-Ge Zhang; Ran Liu; Lu-Yang Tao (Neuroscience Bulletin, 2008)

Identification of 27 Porphyra lines (Rhodophyta) by DNA fingerprinting and molecular markers - Manli Weng; Bo Liu; Demin Jin; Qingkai Yang; Ge Zhao; Jiahai Ma; Pu Xu; Delin Duan; Bin Wang (Journal of Applied Phycology, 2005)

Lack of reversal effect of EDTA treatment on cadmium induced renal dysfunction: a fourteen-year follow-up - Xunwei Wu; Suhua Su; Rihong Zhai; Kekuan Chen; Taiyi Jin; Bo Huang; Yuanfen Zhou; Xianmin Ge; Guoming Wei; Ruiqing Liao (BioMetals, 2004)

Note: A Preliminary Study on Conservation Genetics of an Endangered Orchid (Paphiopedilum micranthum) from Southwestern China - Ang Li; Yi-bo Luo; Song Ge (Biochemical Genetics, 2002)